2020
DOI: 10.1111/ijlh.13229
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and the clinical hematology laboratory

Abstract: The ongoing COVID-19 pandemic originated in Wuhan, Hubei Province, China in December 2019. The etiologic agent is a novel coronavirus of presumed zoonotic origin with structural similarity to the viruses responsible for severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). Like SARS and MERS, COVID-19 infection manifests most frequently with lower respiratory symptoms. A minority of patients progress to acute respiratory distress syndrome/ diffuse alveolar damage. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
275
5
29

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(341 citation statements)
references
References 39 publications
11
275
5
29
Order By: Relevance
“…Conditions such as neutrophilia, lymphopenia and thrombocytopaenia and changes in the levels of markers of systemic inflammation (e.g., neutrophil-to-lymphocyte ratio, NLR), are the most significant quantitative alterations. They have been recognised as valid predictors of disease severity [4,5]. Morphological anomalies of circulating blood cells have also been reported in COVID-19 [6].…”
mentioning
confidence: 96%
“…Conditions such as neutrophilia, lymphopenia and thrombocytopaenia and changes in the levels of markers of systemic inflammation (e.g., neutrophil-to-lymphocyte ratio, NLR), are the most significant quantitative alterations. They have been recognised as valid predictors of disease severity [4,5]. Morphological anomalies of circulating blood cells have also been reported in COVID-19 [6].…”
mentioning
confidence: 96%
“…Severe sepsis is marked by organ dysfunction due to poor blood flow (eg oliguria from poor renal perfusion and altered mental status from poor cerebral perfusion). His laboratory studies showed a consumptive coagulopathy (thrombocytopenia, prolonged PT/aPTT), which, along with bleeding from the IV catheter site and elevated D-dimer, was likely due to DIC [7].…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the cause, lymphopenia is an important factor often associated with SLE patient susceptibility to bacterial and viral infections (33)(34)(35). Interestingly, many COVID-19 patients without SLE exhibit lymphopenia (36). 35-75% (studydependent) of patients who have COVID-19 develop lymphopenia, defined as a lymphocyte count of <1.5 x 10^9/L (37).…”
Section: Lymphopeniamentioning
confidence: 99%
“…35-75% (studydependent) of patients who have COVID-19 develop lymphopenia, defined as a lymphocyte count of <1.5 x 10^9/L (37). Additionally, this clinical finding is a more common feature in patients who died from COVID-19 (36). Furthermore, there seems to be a geographical difference in lymphopenia rates.…”
Section: Lymphopeniamentioning
confidence: 99%
See 1 more Smart Citation